Implementasi Marketing Mix Di Showroom Desata Used Car Dalam Menyusun Strategi Pemasaran - Hanafi, Muhammad Ferdyansyah; Dzulquarnain, Abi Hanif (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to understand the marketing strategy implemented by Desata Used Car Showroom in Gresik, East Java, which uses qualitative methods. The focus of the research is on the meaning and in-depth interpretation of human behavior and social phenomena. The research location is at Showroom Desata Used Car with two main informants: RDC (owner) and AF (inspector and marketing). Primary data was collected through observation and discussion forums, while secondary data was obtained from previous studies. Data analysis was conducted using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The results showed that Desata Used Car has implemented a Marketing Mix strategy consisting of product, price, location, and promotion. The product strategy focuses on diversity to meet changing market interests, while the price strategy is adjusted to the condition of the car units being sold. Although the location of the showroom is not considered important by the owner, marketplace platforms such as OLX play an important role in reaching consumers. Promotion strategies are carried out through social media and marketplaces to increase sales. The conclusion of the study indicates that product and promotion strategies have a significant influence on increasing sales. The recommendation for Desata Used Car is to try a more detailed Marketing Mix strategy, such as 7P or 11P, to optimize their marketing efforts.